Effects of Dexmedetomidine Versus Propofol–Fentanyl on QoR-15 Recovery in Cranioplasty - Fadli, Mhd; Irina, Rr Sinta; Bisono, Luwih (JAI (Jurnal Anestesiologi Indonesia), 2021)
Background: Optimizing postoperative recovery is essential in neurosurgical anesthesia. Dexmedetomidine, a selective α2-adrenergic agonist, may improve sedation and recovery outcomes. This study compared intraoperative dexmedetomidine versus propofol-fentanyl in cranioplasty patients using the Quality of Recovery-15 (QoR-15) score.Methods: A prospective comparative study was conducted at Adam Malik General Hospital and Haji Medan Hospital from May - August 2025 involving 42 adult patients undergoing elective cranioplasty. Subjects were divided into two groups: dexmedetomidine (n=21) and propofol-fentanyl (n=21). Quality of Recovery-15 (QoR-15), a validated 15-item questionnaire assessing five domains of postoperative recovery (pain, physical comfort, emotional state, psychological support, and physical independence; total score range 0–150), was recorded at 12 and 24 hours postoperatively. Hemodynamic parameters, sedation depth, and operator satisfaction were assessed. Data were analyzed using t-tests and Fisher’s exact test with p < 0.05.Results: Patients receiving dexmedetomidine showed higher QoR-15 scores at 12 hours (p = 0.045) and 24 hours (p = 0.003). Heart rate was significantly lower (p = 0.02), while systolic and diastolic pressures showed no significant differences. Sedation depth and operative duration were comparable. Operator satisfaction reached 100% in both groups.Discussion: Dexmedetomidine improved recovery quality compared to propofol-fentanyl, with better hemodynamic stability and fewer sympathetic responses. These findings align with previous studies supporting its use in enhanced recovery anesthesia. Limitations include a small sample size and a lack of intraoperative sedation monitoring.Conclusion: Intraoperative dexmedetomidine offers superior recovery quality and stable hemodynamics, suggesting its potential for broader use in neurosurgical anesthesia.